EFFECT OF EXTENSIVE ROTE LEARNING EXPERIENCE ON SUBSEQUENT ACADEMIC ACHIEVEMENT: Rote Learning Experience - Iqbal, Javed; Ahmad, Amina (Pakistan Armed Forces Medical Journal, 2015)
Objective: To determine the difference between academic achievements in terms of scores of students with prior extensive rote memorization experience with those without it.Study Design: Ex-post fecto studyPlace and Duration of Study: Quaid-e-Azam Medical College, Bahawalpur from Dec 2013 to Mar 2014.Participants and Methods: After Quaid-e-Azam Medical College’s ethical review board’s approval, scores of medical students’ first professional examination were selected by purposive sampling technique, making a total sample size of 102 students, constituting 2 comparison groups with 51 students in each. The first group comprised all the students of 3rd, 4th and 5th year MBBS who were Hafiz-e-Quran and the other one had non Hafiz-e-Quran students from the same year. Descriptive statistics such as mean and standard deviation of their scores were calculated.Results: The overall mean score in biochemistry, physiology and anatomy was statistically different for these two groups as mean scores were 730.25±50.66 and 699.94±48.93 (p = 0.003) respectively for hafiz-e-Quran and non-hafiz-e-Quran. This was because of significant difference in achievement of score in physiology as mean score was 258.47±24.36 and 248.98±20.60 for hafiz-e-Quran and non-hafiz-e-Quran respectively (p = 0.036). The difference in the subject of anatomy and biochemistry was not statistically significant.Conclusion: Prior training of rote learning may provide experience to learn and reproduce bigger chunks of knowledge more effectively